Application of country‐specific Globorisk score to estimate next 10 years risk of cardiovascular diseases and its associated predictors among postmenopausal rural women of Bangladesh: A cross‐sectional study in a primary care setting. Issue 2 (31st March 2021) - Barua, Lingkan; Banik, Palash Chandra; Islam, Sheikh Mohammed Shariful; Faruque, Mithila
Abstract: Introduction: Risk of cardiovascular disease (CVD) among postmenopausal Bangladeshi women has not yet been evaluated using a country‐specific tool. Hence, we prompted to estimate the risk and identify the predictors that were not typically included in any CVD risk assessment tool. Methods: This cross‐sectional study used a web version of country‐specific lab‐based Globorisk calculator to estimate the risk of CVD among 265 postmenopausal women who visited a primary healthcare centre in a rural area of Bangladesh. The centre was selected purposively and the participants were recruited using a convenient sampling technique. Data were collected using a modified STEP‐wise approach to surveillance of non‐communicable disease risk factors questionnaire of the World Health Organization. The risk levels were presented using descriptive statistics and the associated predictors were identified using adjusted multiple linear regression analysis. Results: Overall, 56.7% of the subjects were identified as 'at risk' of future CVD events. After adjusting the confounders, CVD risk factors including age of onset of menopause ( β = 0.441, p < 0.001), duration of menopause ( β = 0.603, p < 0.001), smokeless tobacco use ( β = –1.047, p = 0.003), added salt intake ( β = 1.081, p = 0.002), waist–hip ratio ( β = 0.094, p = 0.03) and diastolic blood pressure ( β = 0.145, p = 0.001) were identified as significant predictors of CVD risk. Conclusion: This finding suggests screening program among postmenopausal women for early detection of CVD risk and efforts to control the associated predictors.